Sensing charcoal making and understanding links to deforestation in Tanzania - Foye, Kabura John (Cranfield University, 2024)
Charcoal making produces atmospheric pollutants that have an impact on human health. In Tanzania, charcoal making activity is widely spread and not properly regulated. The spatial distribution of charcoal kilns is unknown, and this makes management and control of such activity extremely difficult, especially in nature reserves. The aim of this study was to advance current knowledge on environmental impacts (i.e., deforestation and air quality) of charcoal making in Tanzania. The specific objectives were, to develop a methodology to quantify charcoal production emissions in ambient conditions; to identify areas of high- density kilns and changes in charcoal production around the East Usambara Mountains using GIS approaches; and to link charcoal production with catchment impact and degradation. The data analysis involved the isolation of charcoal emission plumes from other regionally important sources, the identification of areas of high-density kilns and changes in charcoal production around east Usambara mountains using GIS-based approaches and the link of charcoal production with catchment environmental impacts. The statistical testing for significant difference in the distribution of concentrations in the pre, during and post periods was identified to comprehend the variation in the observed mean across phases of the testing procedure. The results suggest that there were no statistically significant differences between pre, during and post periods. However, the sensor used in the study was effective in identifying pollutants in tropical regions, despite calibration challenges. The study also identified the sources of pollutants and their trajectories, with southern-eastern winds being a significant factor. Human-induced activities and local emissions were found to contribute to the pollution. The study analysed the emission ratios of pollutants, but found insignificant links between CO and CO2, as well as PM1 and CO2. Furthermore, this study establishes a connection between charcoal production and negative effects on the East Usambara Mountain catchment area. The research findings show that humid forest regions had a significant concentration of proxy variables associated with charcoal production. The study also identifies differences in charcoal-making activities among different forest regions. The prevalence of dark patches indicates a high frequency of charcoal production in the area. The study also reveals a decrease in the quantity of charcoal-making activities between 2013 and 2015, followed by an increase from 2016 to 2019. The study estimates that a significant amount of charcoal was produced, resulting in the harvesting of many trees and the emission of CO and CO2. Overall, the findings highlight the need for sustainable charcoal production practices to mitigate the negative impacts on the surrounding environment. The findings presented in this study demonstrate a mechanism that enables the characterisation of and differentiation between charcoal burning and production signatures. It is recommended that a citizen scale technique developed for detection of emissions and consequence of charcoal making into the community. To investigate strategies to move toward non-fossil fuel sources in Tanzania to reduce pressure on the use of forest. To set up sound regulation around charcoal making activities in Tanzania and development of approaches for sustainable charcoal production in Tanzania.
Harris, Neil R. P. - Associate Supervisor Mead, Iq - Associate Supervisor
Keywords: Deforestation; Charcoal; Electrochemical sensors; Geographical Information System; Catchment management; environmental impact; and degradation